Effective interactive websites: examining the moderating role of involvement - Zotos, Yorgos; Palla, Polyxeni; Tsiotsou, Rodoula H. (My University, 2013)
Consumers’ responses toward an interactive website are moderated by a number of factors. The present study examines whether different levels of product involvement moderate the website interactivity effectiveness in terms attitude formation and pre-purchase intention. Although numerous, previous studies in online environments have either been conducted in a single product sector (e.g. Sicilia, Ruiz and Munuera 2005), or when employing several product categories they did not consider the potential moderating effects of product involvement on the interactivity –attitude formation and pre-purchase intention (Coyle and Thorson 2001; Bezjian-Avery, Calder, and Iacobucci 1998).
Keywords: Interactive websites; Online environments; Moderating effects